EM1‐Signature in the North Fiji Basin: Evidence for Stagnant Slab‐Derived Mantle Upwelling Beneath the Trench‐Distal Back‐Arc Basin. Issue 4 (1st April 2021) - Oh, Jihye; Lee, Insung; Stuart, Finlay M.; Park, Munjae; Kim, Jonguk
Abstract: Basaltic volcanism at the mature back‐arc spreading axis in the North Fiji Basin (NFB) exhibits significant geochemical heterogeneity from depleted mid‐ocean ridge basalt (MORB) to enriched MORB compositions. The volatile and Sr‐Nd‐Pb‐He isotope composition of basaltic glasses from the Central Spreading Ridge (CSR) of the NFB suggests that a second enrichment mantle component is present in addition to the previously observed Samoan mantle plume. The hydrous OIB‐like basalts from the northern CSR have a weak enriched mantle 1 (EM1) isotopic signature and negative correlation between Ba/Th and Zr/Hf ratios, similar to rejuvenated Samoan lavas associated with tectonic driven volcanism. The EM1 signature is distinct from shield‐stage Samoan basalts and back‐arc basin basalts from the Lau Basin by high Ba/La ratio and negative correlation between Ba/Th and Ba/Ta ratios, indicating contributions from dehydrated and altered oceanic crust and sediments. Our new geochemical data suggest that focused melting above the mantle transition zone (MTZ) triggered by dehydration of stagnant slab can be a source of the EM1‐like melts containing both elevated 3 He/ 4 He ratios (up to 12.52  R A ) and altered oceanic slab components. Given the spatial coincidence of the inferred EM1 basalts with the clustered deep earthquakes, our results support the presence of detached oceanic slabs in the MTZ beneath the northern NFB. Plain Language Summary: This work provides interpretation of mantle enrichment process occurred in mature and plume‐distal oceanic back‐arc basins. Providing geochemical data set of basaltic glasses collected from the Central Spreading Ridge in the North Fiji Basin indicates mantle heterogeneity, which can be explained by mixing between the depleted ambient mantle and the enriched mantle reservoir present in the shallow mantle depth. The enriched basalts contain both primordial helium contributed from mantle transition zone (MTZ) and dehydrated oceanic slab component. They are emplaced above deep earthquake clusters indicating slab stagnation in depths of the MTZ. Thus, we suggest focused hydrous mantle upwelling at the edge of detached slabs lying in the MTZ as the shallow origin for the enriched magmatism in plume‐, trench‐distal back‐arc basins. Key Points: New geochemical data of the basalts from the North Fiji Basin reveal a signature of enriched mantle 1 (EM1) near the Fiji Triple Junction The enriched basalts contain both primordial helium inherited from mantle transition zone and dehydrated oceanic slab component Upwelling of hydrous mantle transition zone triggered by stagnant slab can be the source of enriched mantle in mature back‐arc basins